2006
DOI: 10.1016/j.concog.2005.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Flicker-induced color and form: Interdependencies and relation to stimulation frequency and phase

Abstract: Publication InformationBecker, C., & Elliott, M. A. (2006 AbstractOur understanding of human visual perception generally rests on the assumption that conscious visual states represent the interaction of spatial structures in the environment and our nervous system. This assumption is questioned by circumstances where conscious visual states can be triggered by external stimulation which is not primarily spatially defined. Here, subjective colors and forms are evoked by flickering light while the precise nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 29 publications
(40 reference statements)
2
43
2
Order By: Relevance
“…Target colors were those colors reported most reliably in the free-report study described in Becker and Elliott (2006, Experiment 1). These colors have also been tested successfully in a primed response-time paradigm similar to the one employed in the present study (Becker & Elliott, 2006, Experiment 2) and distributions over flicker frequency were found to be very similar. Participants were reminded before each session that a response should only be given to the unequivocal experience of the target color.…”
Section: Design and Proceduresmentioning
confidence: 71%
See 3 more Smart Citations
“…Target colors were those colors reported most reliably in the free-report study described in Becker and Elliott (2006, Experiment 1). These colors have also been tested successfully in a primed response-time paradigm similar to the one employed in the present study (Becker & Elliott, 2006, Experiment 2) and distributions over flicker frequency were found to be very similar. Participants were reminded before each session that a response should only be given to the unequivocal experience of the target color.…”
Section: Design and Proceduresmentioning
confidence: 71%
“…This paradigm was employed with the aim to directly link EEG-frequency changes to the occurrence and report of a specific hallucinatory color. Previous experiments (Becker & Elliott, 2006) have shown that the distribution of color experiences over stimulation frequency are comparable for a free-report and a primed response-time paradigm with a slight overall increase in reports for the primed response-time design.…”
Section: Design and Proceduresmentioning
confidence: 77%
See 2 more Smart Citations
“…We considered it possible that the type of non-specific visual experience reported in blindsight may be reported more often at the temporal frequencies found in previous studies, that is to say at around 20 Hz. Our expectation was based upon other findings in which hallucinatory visual experiences both structured and unstructured are readily induced by stimulus flicker at around 20 Hz (Becker & Elliott, 2006;Becker, Gramman, Müller, & Elliott, 2009). If a non-specific Type II blindsight were found to accompany flicker at 20 Hz, the visual experiences accompanying blindsight might be best characterized in terms of transient hallucinations rather than in terms of the visual experience of stimulus events.…”
Section: Introductionmentioning
confidence: 99%